Economic-ecological services and their trade-offs or synergies of agricultural landscapes in Xiangxi, central China - Hui Xiang (Heliyon, 2023)
The scarcity of agricultural ecosystem services (ESs) caused by land use changes has become increasingly prominent, and the negative effects of agricultural production on ecosystems have been a constant concern. In this work, the geographic information system mapping method, the agricultural product supply (AS) model and InVEST model were applied to assess the economic and ecological services of agricultural landscapes. The interlinkages among them in Xiangxi were explored, a mountainous area in central China. The major conclusions drawn were as follows.1) From 2000 to 2020, the economic services (ESs1) of agricultural landscapes in Xiangxi increased by 96.6667%, and those of grain yield per ha (X1), cash crop output value per ha (X2), forestry output value per ha (X3), meat production per capita in rural areas (X4), and fishery output per ha (X5) were 39.0405%, 510.8462%, 297.6807%, 64.5947%, and 194.0348%, respectively. The spatial distribution of X1, X2, X3, X4, and X5 changed considerably, and the major influencing factors were human elements. 2) Ecological services (ESs2) increased by 5.13%, and those of carbon storage (CS, X6), water conservation (WC, X7), and N content in water (X8) were 1.0897%, 13.5808%, and −0.7406%, respectively. The distribution of X6, X7, and X8 was nearly unchanged and primarily influenced by natural factors 3) The relationship between ESs1 and ESs2 was not ideal. The dominant relationships between AS and CS were trade-offs, those between AS and WC were synergies, and those between AS and water purification were trade-offs. 4) The following suggestions are proposed: promote afforestation and vegetation protection policies, implement the best agricultural policies, increase investment in water conservation projects, adjust agricultural scale, and control the usage of agricultural chemicals. For the surrounding areas of more developed regions, strict environmental measures and agricultural policies are necessary. The methods used in this study are novel and can provide methodological references for similar studies. Moreover, it may offer useful suggestions for agricultural resource management and contribute to ecological civilization construction.